Respuesta :
Answer:
The triangle is both an Isosceles triangle and a right triangle.
Step-by-step explanation:
Given the vertices of a triangle.
[tex]$ P_{1} = (- 1, 4) $[/tex]
[tex]$ P_{2} = (6, 2) $[/tex] and
[tex]$ P_{3} = (4, - 5) $[/tex]
We find the distance between all the points to determine the length of each side of the triangle.
Distance between any two points, say, [tex]$ (x_1, y_1) $[/tex] and [tex]$ (x_2, y_2) $[/tex] is:
[tex]$ \sqrt{\bigg ( \textbf{x}_{\textbf{2}} \hspace{1mm} \textbf{- x}_{\textbf{1}} \bigg )^{\textbf{2}} \textbf{+} \bigg( \textbf{y}_{\textbf{2}} \hspace{1mm} \textbf{- y}_{\textbf{1}} \bigg)^ {\textbf{2}} $[/tex]
Length between [tex]$ P_1 $[/tex] and [tex]$ P_{2} $[/tex] , (Side 1) :
[tex]$ (x_1, y_1) = (- 1, 4) $[/tex] and
[tex]$ (x_2, y_2) = (6, 2) $[/tex]
Distance = [tex]$ \sqrt{\bigg(6 - (-1) \bigg)^{2} \hspace{1mm} + \hspace{1mm} \bigg( 2 - 4 \bigg )^2 $[/tex]
[tex]$ = \sqrt{7^2 + 2^2} $[/tex]
[tex]$ = \sqrt{49 + 4} $[/tex]
[tex]$ = \sqrt{\textbf{53}} $[/tex]
Length of Side 1 = [tex]$ \sqrt{\textbf{53}} $[/tex] units.
Distance between [tex]$ P_1 $[/tex] and [tex]P_2[/tex] , (Side 2):
[tex]$ (x_1, y_1) = (-1, 4) $[/tex]
[tex]$ (x_2, y_2) = (4, - 5) $[/tex]
Distance = [tex]$ \sqrt{ \bigg( 4 + 1 \bigg)^2 \hspace{1mm} + \bigg( - 5 - 4 \bigg ) ^2 $[/tex]
[tex]$ = \sqrt{ 25 + 81 } $[/tex]
[tex]$ = \sqrt{\textbf{106}} $[/tex]
Length of Side 2 = [tex]$ \sqrt{\textbf{106}} $[/tex] units.
Distance between [tex]$ P_2 $[/tex] and [tex]$ P_3 $[/tex] , Side 3 :
[tex]$ (x_1, y_1) = (4, 5) $[/tex]
[tex]$ (x_2, y_2) = (6, 2) $[/tex]
Distance = [tex]$ \sqrt{ 2^2 \hspace{1mm} + \hspace{1mm} 7^2} $[/tex]
[tex]$ = \sqrt{49 + 4} $[/tex]
[tex]$ = \sqrt{\textbf{53} $[/tex]
Length of Side 3 = [tex]$ \sqrt{\textbf{53}} $[/tex] units.
Note that the length of Side 1 = Length of Side 3.
That means the triangle is Isosceles.
Also, For a triangle to be right angle triangle, using Pythagoras theorem we have:
(Side 1)² + (Side 3)² = (Side 2)²
[tex]$ \bigg( \sqrt{53} \bigg )^2 \hspace{1mm} + \hspace{1mm} \bigg( \sqrt{53} \bigg)^2 \hspace{1mm} = \hspace{1mm} \bigg ( \sqrt{106} \bigg ) ^2 $[/tex]
i.e, 53 + 53 = 106
Hence, the triangle is a right - angled triangle as well.